Comparison on Efficiency of Foreign and Domestic Banks Evidence from Algeria - Ishaq Hacini; Khadra Dahou (Journal of Banking and Financial Economics)
The study investigates the differences in technical, pure technical, and scale effi ciencies of domestic and foreign banks in Algeria over the period of 2000–2012. The study uses annual data of 10 foreign banks and 05 domestic banks operated in Algeria. The input-oriented Data Envelopment Analysis model is used to measure the banks’ effi ciency score. In addition, a set of parametric and non-parametric tests are used for investigating the differences in effi ciency between foreign and domestic banks. The fi ndings reveal that the banks in Algeria could improve their technical efficiency by 23%. In addition, it seems that banks in Algeria suffer from the scale inefficiency. On the other hand, the foreign banks are more technically efficient than domestic banks. The superiority of foreign banks in technical effi ciency is due to their superiority in the scale efficiency.